High fashion in the church - Johnstone, Pauline, author.
1 online resource (163 pages, xxxii pages of plates)
Keywords: "The decoration of church vestments, which are the ceremonial garments worn by the clergy at the celebration of the Mass, has always been a matter of high fashion. The aim of this book is to trace the development of decorative style in the vestments through ten centuries, with reference to the influence of fashions in the applied arts in general. It is hoped that the high level of illustration will introduce the reader to a visually exciting and much neglected aspect of the decorative arts"--Page 4 of cover.